The PUF proteins in Trypanosoma brucei - Luu, Van-Duc (2006)
The protozoan parasite Trypanosoma brucei, which causes human sleeping sickness, has to adapt to rather different environments as it cycles between the mammalian host and the tsetse fly vector. This adaptation is mediated by changes in trypanosome gene expression, which are mainly regulated at the post-transcriptional level. Proteins with an RNA-binding "Puf" domain are important for post-transcriptional control by modulation of mRNA stability and regulation of translation in other species. This suggested that Puf domain proteins might also have a similar role in trypanosomes. In addition to the previously characterized TbPUF1 (Hoek, Zanders et al. 2002) I have identified eight more PUF genes in the T. brucei genome. A comparison of the characteristic RNA binding domain of T. brucei PUF proteins suggested that they bind related but distinct targets. Interestingly, each of the PUF protein has an orthologue in Trypanosoma cruzi and Leishmania major. Phylogenetic analysis suggested that there were several kinetoplastid PUF proteins before separation from the eukaryotic lineage. Depletion of each of the nine T. brucei PUF proteins by RNA interference did not result in an obvious phenotypic change. Furthermore, PUF1 knock out procyclic cell lines were viable, indicating that this PUF protein is not essential for in vitro growth. Additionally, double RNAi analyses suggested that the proteins tested did not share redundant functions in T. brucei. Microarray studies comparing wild-type cells with cells where PUF levels have been perturbed (either by RNAi or overexpression) revealed one putative mRNA target for PUF5: CAP17 (corset associated protein 17) mRNA is downregulated upon overexpression of PUF5 in the insect form of the parasite. Interestingly, PUF5 overexpression was also lethal for procyclic cells. Multiple mRNAs which associated with PUF proteins in mRNP complexes were identified. PUF5 for example, selectively binds to mRNAs encoding for amino acid transporters in bloodstream form cells. Attempts to identify PUF interaction partners have so far failed. The effect of PUF proteins on global protein expression level was also investigated using two-dimensional gel electrophoresis approach. A few proteins which were differentially regulated upon RNAi or knockout of PUF proteins were identified. These results indicated that PUF proteins in T. brucei, as is true for PUF proteins in general, are involved in regulating gene expression.
Keywords: Hochschulschrift